Finishing properties of Japanese table by using Kelempayan (Neolamarckia cadamba) / Suraya Yusof and Junaiza Ahmad Zaki - Yusof, Suraya; Ahmad Zaki, Junaiza (2014)
Finishing refers to the final process of furniture manufacturing. The advantage of finishing is to embellishing and protecting the product surface. Finishing consists of two stages that are pre-finish and fully finish. Pre-finish is preparation product surface before applying finishes material by using sandpaper. This process is needed to protect the product from dust, dirt or any unwanted particle and also give smoothness to the product surface. Fully finish is a process of applying finishes material to the product. In this study, two type of system to applying finishes material are used to compare the effect of finishing properties of a Japanese table from Kelempayan wood by using PU Varnish. For system A, the process of sanding and sealer were used two times repeated. While, for system B the process of sanding and sealer were used four times repeatedly. The test had been done for finishing testing are pencil hardness test, tape adhesion test, heat resistant test and household test. The results show that, system B gives better result than system A for finishing properties.